THE PUBLIC AWARENESS OF OVERWEIGHT AND OBESITY AS A RISK FACTOR FOR CARDIOVASCULAR DISEASES - S.V. Shut; Т.А. Trybrat; T.A. Ivanytska; O.O. Goncharova; L.O. Katrychenko (Проблеми екології та медицини)
The cardiovascular pathology is a leading condition in the structure of clinical cases associated with overweight and obesity: more than two-thirds of cardiovascular mortality cases: annually, four million deaths worldwide are associated with a high body mass index (BMI). The awareness among the unorganized population aged from 20 to 82 years in the total number of 280 people was assessed. During the study it was found that overweight and obesity are quite common both among women (20.71 and 16.78%) and men (33.22% and 11.79%, respectively). Among the examined patients, an elevated blood pressure and various changes of the electrocardiogram were detected, of which left ventricular hypertrophy was observed in 57%, which is not only a compensatory reaction, but one of the most important independent factors for the cardiovascular risk. All respondents were offered to attend the Health Promotion School providing the educational program for prevention and correction of the main risk factors for obesity and heart diseases. The principle objective of this program was a change of lifestyle with a primary focus on patients with CVD, increased e physical activity and change of the quality of the diet rather than restricting its caloric value. The second survey was conducted in 6 months and the findings are as follows: BMI was corrected among overweight and obese female patients (14.22 and 13.57%), as well as among male patients (23.21% and 7.5%, respectively), thereby reducing the risk for cardiovascular diseases. The public awareness regarding the risk factors for cardiovascular diseases is considered to be low. Maintaining a healthy lifestyle, rational nutrition and educational program activities are the measures for management of overweight and obese patients resulting in reduction of the risk for cardiovascular diseases.